2021
DOI: 10.21608/ejchem.2021.88648.4263
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antimicrobial Evaluation of New 5-Amino-2,3-dihydrophthalazine-1,4-dione Derivatives

Abstract: 5-Amino-2,3-dihydrophthalazine-1,4-dione (Luminol 1) reacted with some organophosphorus reagents such as phosphonium ylides, trialkyl phosphites, and tris(dialkylamino)phosphines to afford the corresponding olefinic products 5a-e, alkoxy-, and dialkylamino derivatives of Luminol 6a-e. 4-Thioxo-3,4-dihydrophthalazin-1(2H)-one derivative 7 was synthesized from the reaction of Luminol (1) with thiating Lawesson and Japanese reagents. Structures of the synthesized compounds were clarified based on their elemental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…In continuation of synthesis of effective candidates in our laboratory as antimicrobial, antiviral, and anticancer agents [19][20][21][22][23]; we aim to conjugate Ibuprofen with phenyl alanine to be an effective agents as antiinflammatory and analgesic. Our strategy based on preparation of ibuprofen derivatives 1-17 starting from acid chloride 2 that may be expected to have biological activities (Scheme 1).…”
Section: Chemistrymentioning
confidence: 99%
“…In continuation of synthesis of effective candidates in our laboratory as antimicrobial, antiviral, and anticancer agents [19][20][21][22][23]; we aim to conjugate Ibuprofen with phenyl alanine to be an effective agents as antiinflammatory and analgesic. Our strategy based on preparation of ibuprofen derivatives 1-17 starting from acid chloride 2 that may be expected to have biological activities (Scheme 1).…”
Section: Chemistrymentioning
confidence: 99%
“…Recently, Ewies et al [11] reacted of luminol with various phosphorus and thiating reagents indicated the creation of distinct compounds depending on the type of the reagents. The less steric carbonyl group of luminol is the favored attack site.…”
Section: Introductionmentioning
confidence: 99%